Vale to Professor Michael Gaffikin - Parulian Silaen (Australasian Accounting, Business and Finance Journal, 2017)
It is with great sadness that we note the passing of Professor Michael Gaffikin.
Keywords: Vale; Obituary; Professor; Michael Gaffikin; MJR Gaffikin